Kemampuan Menulis Cerita Fantasi Melalui Penerapan Model Pemabelajaran Make-A Match pada Siswa Kelas VII-A SMP Negeri 11 Kupang - Nurasma Bakir; Karus. M Margareta; Semuel Nitbani; Yohanes Febronius Uskono (Jurnal Lazuardi, 2025)
The focus of this study is How is the ability to write fantasy stories through the application of the make a match learning model in class VIIA students of SMP Negeri 11 Kupang The learning model used in this study is make-a match. The purpose of this study is to describe the ability to write fantasy story texts through the application of make-a match learning models. The theory used in this study is the cognitive constructivism learning theory by Jean Piaget, text-based learning and writing theory The method used is a qualitative descriptive research method After conducting research on students, the results obtained that the number of pairs who successfully matched the cartoons was 9 pairs and those who did not succeed in finding their card pairs were 4 pairs. In accordance with four aspects which include aspects of title, structure, linguistic rules, and elements of fantasy story texts. In the student worksheets that have been analyzed, the number of students is 25 people and 25 student worksheets obtained an overall average score of 72. These results can be seen from the percentage of success rate of 72% of students who are quite capable of writing fantasy story texts with scores ranging from 70-100. Students who are said to have completed or exceeded the KKM number 17 people with a percentage of 68% while students who did not complete number 8 people with a percentage of 32%. Thus it can be concluded that the students are capable of writing fantasy stories.